KATEKESE MULTISENSORIK: TEROBOSAN KATEKETIK BAGI INSAN BERIMAN DIGITAL DEWASA INI - Andalas, Mutiara (CREDENDUM: Jurnal Pendidikan Agama, 2019)
This research paper proposes a multisensory catechesis as a catechetical breakthrough for digital believer today. Multisensory catechesis is indebted to digital learner autobiographies that encourage the autobiographical exploration of the Church in catechesis. Fulfilling her call as a catechist of the gospel, the Church activates hearing, sighting and touching sensories to communicate the joy of the gospel. The activation of the multisensory of the faithful generation of now refreshes the dialogue between the Gospel and culture in the digital era. This article "reviews with courage and wisdom, as well as in full loyalty to the content of evangelization, the most suitable and effective efforts to deliver the message of the gospel to people today (Evangelii Nuntiandi No. 40). This field research involved 75 Sanata Dharma Faculty of Science and Technology students to alphabetize autobiography as digital learners. This research measures the level of incorporation of digital technology in their lives as learners.